A new flavanone derivative from the rhizomes of Boesenbergia pandurata. Issue 8 (18th April 2022) - Nguyen, Mai Thanh Thi; Nguyen, Hai Xuan; Le, Tho Huu; Do, Truong Nhat Van; Dang, Phu Hoang; Pham, Tung Van; Giang, Truc Thanh Minh; Sun, Sijia; Kim, Min Jo; Tawila, Ahmed M.; Omar, Ashraf M.; Awale, Suresh; et al.
Abstract: From the methanolic extract of the rhizomes of Boesenbergia pandurata, a new flavanone derivative named (2 R, 7″ S )-8-(1-phenyl-2-carboxyethyl)pinocembrin (1 ) and four known flavonoids (2 –5 ) were isolated. Its absolute configuration was concluded by NMR and MS spectroscopic analysis, together with comparison between experimental and calculated ECD data. In turn, compound 1 exhibited strong cytotoxicity against the PANC-1 human pancreatic cancer cell line with a PC50 value of 6.4 µM under nutrient-deprived conditions, comparable with that of arctigenin (PC50, 0.83 µM). Graphical Abstract: